2020
DOI: 10.1017/s146625231900015x
|View full text |Cite
|
Sign up to set email alerts
|

A review of strategies to impact swine feed biosecurity

Abstract: Global pork production has largely adopted on-farm biosecurity to minimize vectors of disease transmission and protect swine health. Feed and ingredients were not originally thought to be substantial vectors, but recent incidents have demonstrated their ability to harbor disease. The objective of this paper is to review the potential role of swine feed as a disease vector and describe biosecurity measures that have been evaluated as a way of maintaining swine health. Recent research has demonstrated that virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Outbreaks of PEDV in North America were the first events with a potential link between contaminated feed and transmission of disease to pigs (Scott et al, 2016 ). Since then, veterinarians, producers, and feed manufacturers have focused their efforts in preventing biological hazard transmission through the feed supply chain using both prevention and biosecurity strategies (Stewart et al., 2020 ; USDA‐APHIS, 2019 ). Potential solutions to ensure feed safety have routinely included different types of mitigation strategies, either utilizing these strategies alone, or in combination with each other to reduce potential PEDV contamination within the feed (Cochrane et al., 2015 , 2017; Gebhardt et al., 2016 , Schumacher et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Outbreaks of PEDV in North America were the first events with a potential link between contaminated feed and transmission of disease to pigs (Scott et al, 2016 ). Since then, veterinarians, producers, and feed manufacturers have focused their efforts in preventing biological hazard transmission through the feed supply chain using both prevention and biosecurity strategies (Stewart et al., 2020 ; USDA‐APHIS, 2019 ). Potential solutions to ensure feed safety have routinely included different types of mitigation strategies, either utilizing these strategies alone, or in combination with each other to reduce potential PEDV contamination within the feed (Cochrane et al., 2015 , 2017; Gebhardt et al., 2016 , Schumacher et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the high degree of interconnectedness of the feed supply, the current investigation began by evaluating surfaces associated with the manufacture and delivery of swine feed. Additional information reviewing the principles underlying biosecurity plans for feed mills and review of strategies to reduce pathogen transmission through swine feed can be found elsewhere (Cochrane et al., 2016 ; Stewart et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Virus transmission from contaminated ingredients can occur if enough of viable virus survives the production process or is introduced from cross-contamination post-processing from surfaces, dust, foot traffic and other vectors (Stewart et al, 2020). Porcine viruses have been shown to contaminate feed processing facilities, especially dust particles (Schumacher et al, 2017).…”
Section: Strategies To Reduce Risk Of Asfv Contamination In Feed Ingredient Supply Chainsmentioning
confidence: 99%